2015
DOI: 10.1007/s11105-015-0889-3
|View full text |Cite
|
Sign up to set email alerts
|

A Point Mutation of Magnesium Chelatase OsCHLI Gene Dampens the Interaction Between CHLI and CHLD Subunits in Rice

Abstract: Proper chloroplast development and chlorophyll biosynthesis are essential for the photoautotrophic plants. The insertion of magnesium (Mg 2+ ) into protoporphyrin IX (Proto), catalyzed by magnesium chelatase (Mgchelatase), is the first committed step of chlorophyll biosynthesis. In dicot plants, a proposed model revealed that Mg-chelatase I subunit (CHLI) and Mg-chelatase D subunit (CHLD) can interact directly; however, their relation remains elusive in rice, a monocot model plant. In this study, we characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 52 publications
2
42
0
Order By: Relevance
“…Among the 14 samples, the APA profile in 60‐day‐old leaf of indica exhibited dramatic differences from japonica (Figures a and a–c). In 60‐day‐old leaf, four genes with 3′ UTR APA site‐switching events were overrepresented in the pathway of porphyrin and chlorophyll metabolism (Table S5), which has a strong effect on chlorophyll content and photosynthesis in rice (Zhang et al ., , ; Kusaba et al ., ; Sato et al ., ; Kong et al ., ). Among them, two genes exhibiting 3′ UTR shortening in indica , chlorina‐9 ( Chl9 ) and yellow‐green leaf 8 ( YGL8 ; validated by qRT‐PCR in Figure S19a,c), had significantly higher expression levels than those in japonica (Figure a,c, Table S8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 14 samples, the APA profile in 60‐day‐old leaf of indica exhibited dramatic differences from japonica (Figures a and a–c). In 60‐day‐old leaf, four genes with 3′ UTR APA site‐switching events were overrepresented in the pathway of porphyrin and chlorophyll metabolism (Table S5), which has a strong effect on chlorophyll content and photosynthesis in rice (Zhang et al ., , ; Kusaba et al ., ; Sato et al ., ; Kong et al ., ). Among them, two genes exhibiting 3′ UTR shortening in indica , chlorina‐9 ( Chl9 ) and yellow‐green leaf 8 ( YGL8 ; validated by qRT‐PCR in Figure S19a,c), had significantly higher expression levels than those in japonica (Figure a,c, Table S8).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the most noticeable change in APA was observed in the pathway of porphyrin and chlorophyll metabolism, where Chl9 and YGL8 exhibited 3′ UTR shortening and high expression in indica compared with japonica (Figure a,c). Both genes encode the key catalytic subunit of two essential enzymes for chlorophyll biosynthesis and chloroplast development, and their enhanced expression can promote the chlorophyll content and photosynthetic efficiency in rice (Zhang et al ., , ; Kong et al ., ). Correspondingly, in indica , the chlorophyll content and net photosynthetic rate in 60‐day‐old leaf were significantly higher than in japonica (Figure e,f).…”
Section: Discussionmentioning
confidence: 99%
“…AtECB1, which interacts with TRXz and FSD3, regulates plastid gene expression and chloroplast development (Yua et al ). In rice, OsTRXz interacts with OsCHLI (subunit I of magnesium chelatase), which catalyzes the first committed step of chlorophyll biosynthesis (Zhang et al ). TCD5/TSV protects rice chloroplasts from cold stress by interacting with OsTRXz (Wang et al ; Sun et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations to any of these genes may reduce or even eliminate chlorophyll biosynthesis, leading to leaf color changes (Liu et al, 2007, 2016; Yoo et al, 2009; Tian et al, 2013; Wang et al, 2014; Zhang et al, 2015; Yang et al, 2016). Through gene mapping and additional studies, the mutant gene responsible for the xantha marker trait of HYB was identified as a mutated OsGUN4 ( genomes uncoupled 4 ) (Chi et al, 2010; Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%